Arduino Based Multifunction Fan - Muhammad Ulum; Izza Anshory; Dwi Hadidjaja Rasjid Saputra; Shazana Dhiya Ayuni (Procedia of Engineering and Life Science, 2021)
Fans are electronic equipment that are often found in Indonesia, but fan use is generally still used manually. This can cause the use of fans to be ineffective, and again humans must approach the fan in regulating the fan speed according to room temperature and adjusting the fan direction that is right for use. The purpose of this research is to innovate conventional fans into automatic fans to make it easier and more comfortable for humans to operate. This research method is to explain the design of hardware and software as well as the exposure of the experimental tools. The results of this study are that the fan automatically selects the fan speed according to the temperature read by the DHT11 sensor, and if the read temperature exceeds 350C, the system will spray water vapor through a 12V DC pump and stop if the temperature read is below 350C, then the fan will turn on. On / off automatically according to the presence of people around the fan through the PIR sensor, the temperature indicator and the presence of people are displayed on the 16X2 LCD, then for the fan in terms of turning right-left and spraying perfume can be controlled from a distance of 7 meters via IR remote. Where all these systems are controlled via a microcontroller in the form of ARDUINO UNO